Analisis Perencanaan Pembangunan Desa Berbasis RPJMDes: Studi Administrasi Publik di Desa Cibaliung Kabupaten Pandeglang - Suandana, Nana; Bahtiar, Rizal (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This study analyzes village development planning based on the RPJMDes in Cibaliung Village, Pandeglang Regency, from the perspective of public administration. The RPJMDes is understood as a village public policy instrument that reflects decision making processes, stakeholder participation, and the quality of village governance. The method employed is descriptive qualitative through document analysis of the RPJMDes and a conceptual review of public administration, focusing on the village’s vision, mission, policy directions, development programs, planning process, and their alignment with community needs. The findings indicate that procedurally, the RPJMDes has been formulated in accordance with regulations through village deliberations involving the village government, the Village Consultative Body (BPD), and community representatives. However, the substance of the planning remains normative and lacks measurable performance indicators. Development programs are predominantly oriented toward physical infrastructure, while community empowerment, human resource capacity building, and institutional strengthening receive limited attention. Community participation also tends to be formalistic, with planning processes largely dominated by village officials. This condition creates a gap between planned programs and the actual needs of the community, particularly in economic and social aspects. The study concludes that improving the quality of the RPJMDes requires clear performance indicators, a stronger orientation toward empowerment, and more substantive community participation to achieve more responsive and sustainable village governance.